Before Orthodoxy; The Story of Abraham's Sacrifice (Dzabīh) in Early Muslim Commentaries - Azhari Andi; Hamdi Putra Ahmad (International Journal of Islamic Khazanah, 2024)
The story of Abraham's sacrifice holds significant place in Islam, and what Muslims believe about Ishmael as the intended sacrifice is not the only belief in the Muslim tradition. This paper examines the historical transformation of Abraham’s sacrifice narratives in Muslim commentaries (tafsīrs), with a focus on revealing how, when, why, and at whose hands this transformation occurred. Employing the theory of tafsir as a genealogical tradition of Walid A. Saleh and adopting a socio-historical approach, this paper investigates the evolution of the interpretation of the story of dzabīh from Isaac to Ismael and the factors contributing to this evolution. The analysis reveals that in the first four centuries of Islam, Muslim interpretations and attitudes regarding the story of dzabīh were the complete opposite of what is common today. Muslim commentators, such as al-Suddī, Ibn Juraij, Muqatil ibn Sulaiman, al-Thabarī, and al-Samarqandī, firmly believed that Isaac is dzabīh. However, Ibn Athiyyah and al-Baghawī, the commentators of the sixth century hijri, showed different responses towards this story, neutral and favoring Ismael as dzabīh. Additionally, in the eighth century Hijri, Ishmael as dzabīh gained orthodoxy and popularity, as demonstrated by Ibn Taimiyyah and Ibn Kathir. They condemned the pro-Isaac as heretical interpretation and rejected it. Even though they disagree with the proIsaac commentators, they still quoted the narrations and opinions of previous commentators by providing counter-arguments, and this is what is called tafsir as a genealogical tradition. Furthermore, power dynamics and the socio-political setting of the eighth century may have had an impact on this change in the story of dzabīh. This evolution highlights the dynamic nature of Islamic interpretation, where interpretation is not necessarily static but evolves over time, shaped by historical contingencies and socio-political dynamics. This historical reevaluation illuminates the complexity of Islamic intellectual history and the fluidity of religious interpretation in the Muslim tradition.